Penguatan Pemahaman Literasi Keuangan di Era Smart 5.0 kepada Siswa MAN Kabupaten Karimun - Catur Fatchu Ukhriyawati; Sri Mulyati; Paras Faturohim; Lukmanul Hakim; Ramon Zamora; Ravika Permata Hati; Celina Cicilia Margaritha; Pohan, Albert Efendi (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The Smart 5.0 era, characterized as the pinnacle of technological transformation, necessitates continuous improvement in individuals' comprehension and literacy competency, particularly in financial literacy. Financial literacy encompasses an individual's abilities, knowledge, attitudes, and behaviors related to managing personal monetary assets. However, empirical evidence suggests that students, especially in disadvantaged areas, demonstrate a limited understanding of financial literacy. This Community Service was conducted with the objective of enhancing financial literacy comprehension among MAN students in the Karimun Regency. The activity took place in MAN Karimun Hall on August 26-27, 2024, with 220 students in attendance. The PKM method is carried out through face-to-face training activities by implementing the management functions of planning, organizing, implementing, controlling, and evaluating. The evaluation of this community service program the following outcomes: 1) The financial literacy strengthening program was implemented effectively in accordance with established plans. 2) Students demonstrated comprehension of the financial literacy material presented by the speakers. 3) Students also exhibited an understanding of the significance of developing financial literacy competencies (personal finance) from an early age in the Smart 5.0 era, enabling them to manage and plan their finances optimally in the future. This PKM still focuses on improving the understanding of financial management at the MAN student level, and further PKM needs to be carried out starting with elementary and junior high school students so that MAN students are not late in understanding financial literacy competencies.